2022
DOI: 10.1007/s43621-022-00086-7
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to climate variability of productive livelihoods in the Talgua watershed, Honduras.

Abstract: This research aims to analyze the vulnerability of productive agricultural livelihoods to the effects of climate variability in the Talgua watershed, Honduras. Information was collected through surveys and interviews with small producers and community leaders. A factor analysis (KMO test value 0.721; Bartlett’s test of sphericity (P > 0.000) was conducted to identify the relevant variables describing productive livelihoods, and vulnerability was analyzed according to the perception of small producers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, these climatic conditions have led to the emergence of pests and diseases and have made it difficult for communities to transport and sell agricultural products, further exacerbating the situation in the region. At the same time, a decline in natural soil fertility has been observed, which was attributed to changes in land use and the action of erosive processes [59,76]. In 1998, 2005, and 2008, the study area was affected by high rainfall events caused by hurricanes Mitch, Beta, and tropical depression 16 (Figure 6), and more recently, in 2020, hurricanes Eta and Iota.…”
Section: Pressures On Ecosystem Services (Water) In the Talgua River ...mentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, these climatic conditions have led to the emergence of pests and diseases and have made it difficult for communities to transport and sell agricultural products, further exacerbating the situation in the region. At the same time, a decline in natural soil fertility has been observed, which was attributed to changes in land use and the action of erosive processes [59,76]. In 1998, 2005, and 2008, the study area was affected by high rainfall events caused by hurricanes Mitch, Beta, and tropical depression 16 (Figure 6), and more recently, in 2020, hurricanes Eta and Iota.…”
Section: Pressures On Ecosystem Services (Water) In the Talgua River ...mentioning
confidence: 98%
“…Sandoval et al [76] identified other climate-related pressures in the Talgua River watershed (Figure 6). The livelihoods of farmers in the area have been affected by increased temperatures, reduced rainfall, heat waves, or heavy rains, resulting in economic losses of Coffea arabica, Zea mays, and Phaseolus vulgaris crops.…”
Section: Pressures On Ecosystem Services (Water) In the Talgua River ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The frequent occurrence of floods and droughts is evidence [11,12]. Even residential areas and public infrastructure were inundated by floods, causing extensive material and non-material damage and losses [13,14].…”
Section: Introductionmentioning
confidence: 99%